(untitled) (Research, Society and Development, 2023)
Introduction: Pharmaceutical assistance is a set of actions aimed at the promotion, protection, and recovery of health, both individual and collective, having the drug as an essential input and aiming at access and its rational use. Objective: To investigate how Pharmaceutical Assistance is institutionalized in Benevides, 1st Health Region of the State of Pará. Method: It is an exploratory, retrospective-prospective, descriptive-analytical study, carried out between 2021 and 2022, based on action research and triangulation of methods. Data were collected through database research and the application of structured forms. Results: It was observed that pharmaceutical assistance is included within the main planning and management instruments of the Unified Health System; there is no stock control management system via the Horus system. Does not fully comply with management, management, and governance practices at the pharmaceutical care coordination level, especially in the field of technical management of pharmaceutical care and clinical management of medication. Conclusion: Pharmaceutical Assistance is institutionalized in the municipality of Benevides, but it needs to consolidate and strengthen the governance and management process, where there are still gaps in technical-management and technical-assistance issues.